Isavuconazole - Takazono, Takahiro; Tashiro, Masato; Izumikawa, Koichi (Nihon Ishinkin Gakkai Zasshi, 2025)
Isavuconazole, a second-generation triazole antifungal, is indicated for the treatment of invasive fungal infections, including aspergillosis and mucormycosis. It is administered as the water-soluble prodrug isavuconazonium sulfate, which is rapidly hydrolyzed in the body to produce the active compound, isavuconazole. The drug is available in both oral and intravenous formulations, offering high bioavailability and stable pharmacokinetics. Isavuconazole exhibits broad-spectrum antifungal activity, with efficacy comparable to voriconazole in treating invasive aspergillosis, while also being effective against mucormycosis. Notably, it requires no dose adjustments in patients with renal impairment, and routine therapeutic drug monitoring is generally unnecessary. The drug’s safety profile is favorable, with no observed risk of QTc prolongation and fewer drug-drug interactions compared to other azoles. Its high tolerability often makes it the agent of choice for patients transitioning from other azoles due to adverse effects. This review provides a comprehensive overview of isavuconazole’s mechanism of action, antifungal spectrum, pharmacokinetics, resistance mechanisms, tissue distribution, and clinical applications, highlighting its role in the management of invasive fungal infections.